Synthesis and Characterization of Nano SnO2 Modification on LiNi0.8Mn0.1Ni0.1O2 Cathode Materials for Lithium Ion Batteries - Wang, Chunxiang; Peng, Wanwan; Li, Zhifeng; Liang, Yali; Zhong, Shengwen; Zhang, Qian (Frontiers in Energy Research, 2019)
Abstract: The precursor material of Ni0.8Co0.1Mn0.1(OH)2 was prepared by a co-precipitation method to obtain the layered cathode materials LiNi0.8Co0.1Mn0.1O2 (811) through roasting with LiOH·H2O. Then the SnO2-modified samples were obtained by adding tin oxide into the ball mill. It was found by XRD characterization of the original and modified samples, that the addition of SnO2 did not change the layered structure of the raw materials. Microstructure and distribution of the SnO2 were analyzed with SEM and EDS. Charge/discharge tests indicated that the SnO2-modified phases improved the cycling stability and rate capability. The results of CV test showed that the polarization of SnO2 modified electrode was smaller. AC impedance showed that SnO2/LiNi0.8Co0.1Mn0.1O2 electrode had smaller Rct and Rf value. The above test results indicate that the modification of SnO2 improves the electrochemical performance of cathode material LiNi0.8Co0.1Mn0.1O2.